Phosphazene Tripeptide Conjugates: Design, Synthesis, In Vitro Cytotoxicity and Genotoxicity, Molecular Interactions in Binding Pockets on Human Breast and Colon Cancer Cell Lines - Caliskan, Eray; Yuksel, Furkan; Capan, Irfan; Tekin, Suat; Bouzidi, Reda; Qaoud, Mohammed T.; Gorgulu, Ahmet Orhan (Wiley-V C H Verlag Gmbh, 2025)
The biological activity of both cyclophosphazenes and peptides makes these compounds important for new studies in medicinal chemistry. For this purpose, five different phosphazene-peptide conjugates synthesized from dichlorocyclotriphosphazene and tyrosine-containing tripeptides. The synthesized compounds were evaluated for their in vitro cytotoxic activities against human breast (MCF-7) and colon (Caco-2) cancer cell lines using MTT assay. The derivatives induced cell death through DNA damage, with notable effects in Caco-2 cell lines. Specifically, DTVV, DTVG, and DTVA were cytotoxic at 50 and 100 mu M, while DTVP and DTVM were effective at 25, 50, and 100 mu M. DTVM outperformed Tamoxifen at 50 mu M in the MCF-7 cell line. DNA damage studies of the compounds were performed using the comet assay method, evaluating tail length, tail density, olive tail moment, head length, and head density parameters. The findings indicated that cell death occurred via a DNA damage mechanism. The molecular intricacies of DTVA, DTVG, DTVM, DTVP and DTVV within the VEGFR2 kinase domain (3VHE) and Cyclophilin_CeCYP16-Like Domain (2HQ6) binding pockets and various interactions, docking scores and potential activities of these derivatives were investigated. The differences in docking scores and interaction profiles highlight the potential efficacy and specificity of these compounds in targeting breast and colon cancer cells. These findings highlight the potential of phosphazene-peptide derivatives as therapeutic agents in cancer treatment.
Keywords: Tripeptides; Phosphazene; Molecular docking; Cytotoxicity; Genotoxicity